Sensitivity of mass-independent Sn isotope fractionation to UV radiation and magnetic fields - Jia-Xin She; Weiqiang Li; Shujuan Zhang; Cheng Gu; Xiru Chen; Hongcen Zheng; Cheng Xu; Wei Liu (Proceedings of the National Academy of Sciences, 2025)
Mass-independent isotope fractionation (MIF) enables powerful geochemical tracers for various geological and planetary problems, yet the mechanisms driving MIF for tin (Sn) remain ambiguous. Here, we demonstrate that distinct Sn isotope fractionation signatures were produced during photolysis of organic Sn species (i.e., methyltin) under laboratory UV irradiation and natural sunlight. UV irradiation of methyltin induced pronounced Sn-MIF in all odd Sn isotopes (Δ 115 Sn up to 21.82‰, Δ 117 Sn up to 23.16‰, Δ 119 Sn up to 24.01‰), with their ratios (Δ 117 Sn/Δ 115 Sn = 1.069; Δ 119 Sn/Δ 115 Sn = 1.099; Δ 119 Sn/Δ 117 Sn = 1.028) strongly correlating with nuclear magnetic moments. This unambiguously identifies the magnetic isotope effect (MIE) as the driving mechanism, ruling out other causes such as the nuclear volume effect (NVE). Methyl radicals (•CH 3 ) were detectable during the methyltin photolysis experiments, and the magnitude of MIF for Sn was suppressed by the presence of electron spin trapping agent (DMPO) for radicals, supporting that the pronounced Sn-MIF originated from radical-mediated singlet-triplet state transitions of Sn species. Furthermore, the magnitude of Sn-MIF depended nonmonotonically on external magnetic fields (peak suppression at 100 to 180 G), implying competition between hyperfine coupling and Zeeman interactions. Notably, Sn-MIF was absent during photolysis of methyltin by natural sunlight despite significant mass-dependent Sn isotope fractionation (e.g., >3‰ in δ 122/116 Sn), attributed to atmospheric ozone shielding of short-wavelength UV (<290 nm) required for radical generation. Our results register Sn-MIF as a sensitive tracer of UV-driven photochemistry in low-oxygen environments, underlining the potential of Sn isotopes in studies of early Earth’s atmosphere and planetary environments.